Java servlet programming : 2nd edition - Hunter, Jason, ....-; Crawford, William, 1978- (Sebastopol (Calif.) : O'Reilly, 2001)
Samenvatting:The second edition of this popular book has been completely updated toadd the new features of the Java Servlet API Version 2.2, and newchapters on servlet security and advanced communication. In addition tocomplete coverage of the 2.2 specification, we have included bonusmaterial on the new 2.3 version of the specification
Keywords: Java (Computer program language).; Java (programmeertaal).; Servlets